The role of native vegetation on infection rates of Calacarus heveae (Acari: Eriophyidae) by Hirsutella thompsonii (Ascomycota: Ophiocordycipitaceae) - Nuvoloni, Felipe Micali [UNESP]; Castro, Elizeu Barbosa de [UNESP]; Fazzio Feres, Reinaldo Jose [UNESP] (Springer, 2014)
Hirsutella thompsonii (Fischer) (Ascomycota: Ophiocordycipitaceae), a fungal pathogen, often causes high mortality in populations of Calacarus heveae Feres (Acari: Eriophyidae), an important pest mite in rubber tree plantations (Hevea brasiliensis Muell. Arg., Euphorbiaceae). However, the ecological and climatic factors regulating this host-pathogen system are poorly known. We compared fungal infections in agroforestry and traditional rubber plantations to evaluate the role of native vegetation and climatic factors on infection rates of C. heveae by H. thompsonii. While the prevalence of H. thompsonii was higher in managed rubber tree plantations, the abundance of C. heveae was about three times higher in traditional plantations. Abundance of C. heveae, agroecosystem management type and microclimatic variables were responsible for driving the infection rates of H. thompsonii. Native vegetation was a source for H. thompsonii and also modified the crop's microclimate, which contributed to its maintenance in the crop fields. Therefore, appropriate management practices may enhance the effects of entomopathogens on conservative biological control of pest mites in agroforestry systems.
Keywords: Ecological management; Entompathogen; Hevea brasiliensis; Pest mite